Analysis of Students Algebraic Thinking Ability viewed by Auditory Learning Style - N Mahanani; N Priatna; A Jupri (Pascasarjana Universitas Pendidikan Indonesia, 2020)
This study aimed to find out an overview of students algebraic thinking abilities viewed by auditory learning styles in one of the junior high schools in Bandung. This research is motivated by the results of studies that show varying ability (high, medium, and low) of junior high school algebra, so it is necessary to know the cause, and one of the causes is learning style. The subjects in this study were three students with auditory learning style. This research used a qualitative method. The data was collected using: learning style questionnaire, essay test, interview, and documentation. The results show that students who have auditory learning styles tend to answer with explanations in the form of sentences so that they can clarify what they mean or what they understand. Students who have auditory learning styles are able to fulfill indicators in algebraic thinking skills: conceptually based on computational strategies, manipulating numbers and symbols using algebraic rules, and expressing generalizations of patterns and rules in real-world contexts. Based on this research, the researcher suggested that the students can be facilitated with appropriate learning methods or models to contribute well to their algebraic thinking abilities.